Epidemiological features and management of eye burn patients in Wuxi, China. Issue 1 (3rd February 2023) - Lu, Zijing; Chu, Ting; Yang, Zhi-Hui; Xia, Xin; Shen, Yi-Hui; Chen, Jian-Huan; Wang, Ji-Hong
Abstract : Background: The current study aimed to analyse epidemiological data on eye burns in Wuxi, China, for the years 2015–2021, and to provide insight into the development of appropriate prevention strategies. Methods: A retrospective study was conducted on 151 hospitalised patients with eye burns. Data collected included gender, age, the monthly distribution of incidence, cause of eye burn, the site of eye burn, the type of surgery, visual outcome, the length of hospital stay and the cost of hospital admission. Statistical analysis was performed using SPSS V.19.0 and Graph Pad Prism V.9.0. Results: In a total of 151 eye burn patients, 130 were males (86.09%) and 21 were females (13.91%). The proportion of patients classified as grade III was the greatest (46.36%). The average age of our hospitalised patients with eye burns was 43.72 years and the average length of hospital stay was 17 days. The number of injuries was highest in September (14.6%). Among eye burn patients, workers and farmers became the most common occupations (62.91%, 12.58%). The most frequent cause of burns was alkali burns (19.21%), followed by acid burns (16.56%). When admitted to the hospital, patients' average vision was 0.06, and 49% of them had a poor vision (<0.3, ≥0.05). Conclusion: With an investigation of 7-year hospitalisation data, the current study provided a fundamental reference for epidemiological features and management of eye burns in Wuxi, China, which could contribute to the development of treatment and prevention strategies.